Organization Communicational In Islamic Boarding School (On Process) - Sidiq Rifai; Bambang Setyo Utomo (Sahafa Journal of Islamic Communication, 2022)
Organizational climate is a situation in an organization, where each member interacts with each other, limits themselves, or interacts with each other so as to improve the quality of cooperation and organizational satisfaction. Organizational satisfaction is the satisfaction of members of the organization regarding their work, supervision, wages and profits, assessment of achievements, and peers. The purpose of this study was to determine the relationship between the organizational communication climate and organizational satisfaction in the dormitory of Al Azhar Pondok Modern Darussalam Gontor Kampus 2 Madusari, Siman, Ponorogo. This research uses a survey method with an explanative type of research. The population of this study was new students in the dormitory of Al Azhar Pondok Modern Darussalam Gontor Campus 2 with a total sample of 115 students. The sampling technique is carried out by cluster random sampling. The results showed a correlation relationship with the degree of "quite strong" relationship with the form of a positive relationship between the organizational communication climate and organizational satisfaction. This is evidenced by the value of the correlation coefficient value of 0.558 or 55.8%. The variables of the organizational communication climate have a significant influence on organizational satisfaction, while the magnitude of the influence of the organizational communication climate on organizational satisfaction is 31.1% while the other 68.9% is influenced by other factors. This study recommends to the administrators of the Al Azhar Dormitory Pondok Modern Darussalam Gontor Campus 2 to further improve the organizational climate on indicators of joint decision making and organizational satisfaction on satisfaction indicators of achievement assessment, promotion, and job opportunities.